Binuclear Ni(II), Co(II), VO(II) and Pt(II) Chelates of Bidentates Possessing N-N-S Moieties - Gaur, Santwana; Sharma, Beena (Asian Journal of Chemistry, 2010)
Metal-chelates of Co(II), Ni(II), Cu(II), VO(II) and Pt(II) with N-(3)-pyridine carboxaldeimino)benzene thiol (HPCBT) and N-(3-pyridine carboxaldeimino) ethane thiol (HPCET) were synthesized and characterized by elemental analysis, molar conductance, magnetic moment IR and thermogravimetric analysis. These chelates exhibited sub-normal magnetic moments at room temperature indicating magnetic interaction between the metal(II) centres via bridging thiolic sulphur.